Transfusion in the Newborn - Sunarto Sunarto (Paediatrica Indonesiana, 1991)
Transfusion, either with whole blood or blood components is frequently needed in the neonatal intensive care. Certain aspects are very important to consider. Citrated blood is prefered to heparinized blood. Transfusion must be rational, either with whole blood or blood components. Whole blood is only indicated for repletion of blood volume, exchange transfusion and certain cases in which no blood component needed is available.To improve oxygen carrying capacity, to stop bleeding due to coagulation defect, thrombocytopenic bleeding due to depressed platelets production and to counter gram negative septicemia, blood component is indicated to obtain optimal effects with minimal side effects.